2016
DOI: 10.1177/1071100716674671
|View full text |Cite
|
Sign up to set email alerts
|

Association of Abnormal Metatarsal Parabola With Second Metatarsophalangeal Joint Plantar Plate Pathology

Abstract: Level III, retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Although the variability in loading predicted by the various regression analyses was not large (4%-14%), the relative length of the second metatarsal (to the first and to the third) was maintained in each of the regression models and remained the strongest predictor, with the highest standardized β-coefficients, in each of the models. These findings are important because although elongated second metatarsals are generally believed to increase the risk for developing progressive plantar plate injuries beneath the second MTP joint, 1,2,12,13,[20][21][22][23]30,31,34 some authors have disputed the role of a long second metatarsal and suggest that plantar loading characteristics are largely unaltered by metatarsal length. 11,16 In a prospective study examining 46 patients with metatarsalgia and 45 patients without metatarsalgia, Kaipel et al 16 reported that loading of the first and third metatarsals did not correlate with relative metatarsal length.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the variability in loading predicted by the various regression analyses was not large (4%-14%), the relative length of the second metatarsal (to the first and to the third) was maintained in each of the regression models and remained the strongest predictor, with the highest standardized β-coefficients, in each of the models. These findings are important because although elongated second metatarsals are generally believed to increase the risk for developing progressive plantar plate injuries beneath the second MTP joint, 1,2,12,13,[20][21][22][23]30,31,34 some authors have disputed the role of a long second metatarsal and suggest that plantar loading characteristics are largely unaltered by metatarsal length. 11,16 In a prospective study examining 46 patients with metatarsalgia and 45 patients without metatarsalgia, Kaipel et al 16 reported that loading of the first and third metatarsals did not correlate with relative metatarsal length.…”
Section: Discussionmentioning
confidence: 99%
“…25 This particular forefoot measurement of metatarsal parabola has been described as being more reliable than Hardy and Clapham's arc method 14 and has previously been found to correlate with increased risk for plantar plate injury. 4,13,22 AP radiographs were also analyzed for absolute length of the second metatarsal ( Figure 2), metatarsus adductus angle, first and second intermetatarsal (IM) angle, talocalcaneal angle, and hallux abductus angle as previously described. 8,19 Lateral radiographs were examined for first and second IM angle, calcaneal inclination angle, talar declination angle, first metatarsal declination angle, Seiberg index, and hallux equinus angle.…”
Section: Radiographic Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Most recently, Fleischer et al associated the elongated second metatarsal as a significant finding in plantar pathology and previously advocate for metatarsal shortening with plantar plate repair. 16 While shortening osteotomies are a viable option for correction, the described technique does not necessitate any osseous procedure.…”
Section: Discussionmentioning
confidence: 99%
“…6 A positive index implied that the first metatarsal was longer than the second. Fleischer et al 10 reported that MPI less than −4 mm may be associated with a 2.5 times greater risk of developing plantar plate pathology that would cause deformity of the second ray. 11 MPD was defined as the distance from the apex of the second metatarsal to a line connecting the apex of the first and third metatarsals ( Figure 3).…”
Section: Methodsmentioning
confidence: 99%